The crime, mental health, and economic impacts of prearrest diversion of people with mental health problems: A systematic review. (10th April 2019) - Schucan Bird, Karen; Shemilt, Ian
Abstract: Background: Prearrest diversion strategies are being adopted across the Western world, enabling the police to identify and divert people suspected of having mental disorder towards health and community services rather than the criminal justice system. Aims: To quantify longer‐term criminal justice and mental health outcomes after prearrest diversion of people with suspected mental disorder and consider economic correlates. Methods: A systematic review of published literature on longer term outcomes after prearrest diversion. Results: Only two quasi‐experimental studies, with four independent samples, could be included. Findings for criminal and mental health outcomes were inconclusive, but potential for adverse outcomes was identified. Ten studies with cost data suggested that prearrest diversion can lead to overall cost savings. Conclusions: There is still inadequate evidence on which to base prearrest diversion programmes. Although some benefits have been identified by the review, so have possible harms. Future research and funding strategies must build in high‐quality, systematic evaluation of outcomes before implementing a theoretically attractive strategy more widely.